Note on extension of the Young’s formula to inhomogeneous columns - Elishakoff, Isaac (Vietnam Journal of Mechanics, 2020)
In this Note the generalization of the celebrated formula by Young, applicable to homogeneous columns, is provided for inhomogeneous columns.